Maternal Immunologic and Clinical Response to Antiretroviral Therapy Initiation Before or During Pregnancy in HIV-1 Infected Women and associated factors in Southwest Ethiopia - Ijigu, Girma; Gemeda, Desta; Angamo, Mulugeta (Gülhane Tip Dergisi, 2015)
The aim of this study is to assess maternal treatment outcomes to antiretroviral therapy initiated before or during pregnancy in HIV-1 infected women and associated factors in southwest Ethiopia. Hospital based retrospective cohort study was conducted from January 1st 2008 to December 31st 2012.The data were processed using SPSS version 16 (Chicago: SPSS Inc., 2007). A p-value of